Strategi Pendukung Pelaksanaan Peremajaan Kelapa Sawit di Provinsi Jambi - Siti Abir Wulandari; Zulkifli Alamsyah; Dompak Napitupulu; Ardi Novra (Jurnal MeA (Media Agribisnis), 2023)
Efforts to accelerate oil palm replanting in Jambi Province are constrained due to internal and external factors that greatly affect oil palm farmers. The total area of oil palm plantation in 2022 in Jambi Province is 1,099,191 ha consisting of 201,835 ha of immature plants, 759,455 ha of yielding crops and 137,902 ha of damaged or old plants. Oil palm replanting needs to be done considering to the age of oil palm which has got unproductive period. Information on internal and external factors is needed to provide solutions to the obstacles faced by smallholders in oil palm replanting. These two factors influence the decision of farmers to rejuvenate their oil palm and find alternatif strategic options that can be done in order to accelerate the replanting of oil palm plantations in Jambi Province. The study design is cross sectional. The data analysis method used in this study is  SWOT analysis